Impact of Teacher-Student Relationship on Motivation levels & Academic Performance in Learning Chinese as a Second Language among Pakistani Students - Nawaz, Nimra (European Scientific Journal, ESJ, 2023)
The purpose of this study was to examine the effect of Teacher Student Relationship (TSR) on Pakistani students’ motivation and academic performance in a Chinese as a Second Language class. The sample of the study consists of 80 Chinese-language elementary school students. A total of three research questions and hypotheses were used in the study. A pre-post-test design was used to achieve the objectives of the study in which special treatment was given to the experimental group, whereas no treatment was given to the control group. SPSS was used as a statistical tool to examine the results of the present research. The results of the study proved the effectiveness of TSR in improving students’ motivation and academic achievement, as the experimental group showed a better performance in the post-test than the control group. Moreover, the correlation test results indicated a positive significant relation between the TSR, academic performance, and student motivation.